A PENINGKATAN MINAT BELAJAR SISWA KELAS IV SD ISLAM DARUL HUDA MELALUI PEMBELAJARAN BERDIFERENSIASI - Fikriyyah, Sefi Amiqotun; Sari, Yunita; Ulia, Nuhyal (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This research is motivated by the lack of effectiveness of the teaching methods used, which are still limited and do not meet the needs and characteristics of the students. To address this, the researcher will implement a differentiated learning approach to enhance students' interest in learning. The aim of this study is to determine how effective the implementation of differentiated learning, tailored to the individual needs of students, is in improving the learning interest of fourth-grade students in the IPAS subject at SD Islam Darul Huda through the implementation of the Field Experience Practice II in the Teacher Profession Education Program. This study employs Classroom Action Research (CAR) conducted in two cycles. The research was carried out at SD Islam Darul Huda, involving 20 fourth-grade students as the subjects. Data collection techniques include observation, documentation, and questionnaires. Meanwhile, the data analysis techniques used are quantitative and descriptive qualitative analysis. The results of the study indicate that the percentage of students' interest in learning in the pre-cycle was 58.75%, increased to 78.05% in cycle 1, and further rose to 92.25% in cycle 2. Thus, the implementation of differentiated learning has proven successful in improving the learning interest of fourth-grade students in the IPAS subject at SD Islam Darul Huda.